Clinical Features and T Cell Immune Characteristics of Postpartum Hepatitis Flare in Pregnant Women With HBeAg-Positive Chronic HBV Infection - Song, Aixin; Liu, Yisi; Cao, Zhenhuan; Lu, Junfeng; Ren, Shan; Zheng, Sujun; Ma, Lina; Hu, Zhongjie; Lin, Xiao; Li, Hong; Zheng, Yanhong; Chen, Xinyue (Frontiers in Immunology, 2022)
Background The extent of the increase in postpartum alanine transaminase (ALT) varies significantly among pregnant women in the immune tolerance stage of nucleoside analogue (NA) intervention, so this study is an attempt to analyze the clinical features of patients with and without postpartum hepatitis flare and preliminarily explore the differences in their immune functions. Methods Pregnant women with a gestational age of 24–28 w and in the immune tolerance stage of NA intervention for hepatitis B virus (HBV) infection were included and divided into a hepatitis group (Group 1) and a nonhepatitis group (Group 2) according to the ALT level at 6–12 w after childbirth. The clinical features were analyzed, and the phenotypes, functions, and cytokines of clusters of differentiation CD8+ T cells in the two groups of patients were detected using flow cytometry before and after childbirth. Results A total of 15 patients with postpartum hepatitis flare were enrolled in Group 1, and 10 matched patients were selected as controls for Group 2. Compared with the individuals in Group 2, the postpartum clinical features in Group 1 included a remarkable elevation of the ALT level on the basis of a relatively low HBV DNA level, usually accompanied by a decline in hepatitis B virus surface antigen levels as well as HBeAg levels. In addition, CD8+ T cell activation was enhanced after childbirth in Group 1. In particular, there was a notable difference in the activation of Teff subsets, and the frequency of CD8+ T cells expressing perforin and granzyme B increased. Conclusion The changes in the immune characteristics of CD8+ T cells may play a certain role in breaking down immune tolerance in patients with postpartum hepatitis flare, and the indexes related to activating and killing functions may help to indicate the population with hepatitis flare after childbirth.